Morfología de Limonium sinuatum (L.) Miller (Plumbaginaceae) - Oviedo de Blas, I (Universidad de Costa Rica, 1992)
The morphology of statice, Limonium sinuatum (Midnigbt Blue), was studied in San José, Costa Rica, under greenhouse conditions, and in tite field. The germination rate was determined for husked seeds placed in petri dishes 011 mom papero The germination was rapid; epigeal, phanerocotylar or CJYPfOCOtYlar, the latter being tite most frequent Morphological variations were maracteristic of earo Ptysiological state. There is a deep main root of woody consistency, witlt many seconda¡y roots, chiefly in tite upper 10 cm of soíl. The floral stem is a polytelic synflores cence, bracteate, open type, similar lO an open panicle corymbose. The diameter and vigor of tite roseUe varied considerably, as did tite sbape of tite planto sbape of leaf, color, ahape and number of bracts, and.tlte morphology, size, weigbt and number of floral stems, both within a plant and amoog plants. The vegetative period was 105-120 days and the pre-flowering period lasted 30 days; flowering (anthe